Neurophotonics Approaches for the Study of Pattern Separation - Morales, Cristian; Morici, Juan Facundo; Miranda, Magdalena; Gallo, Francisco Tomás; Bekinschtein, Pedro; Weisstaub, Noelia V. (Frontiers in Neural Circuits, 2020)
Successful memory involves not only remembering over time but also keeping memories distinct. Computational models suggest that pattern separation appears as a highly efficient process to discriminate between overlapping memories. Furthermore, lesion studies have shown that the dentate gyrus (DG) participates in pattern separation. However, these manipulations did not allow identifying the neuronal mechanism underlying pattern separation. The development of different neurophotonics techniques, together with other genetic tools, have been useful for the study of the micro-circuit involved in this process. It has been shown that less-overlapped information would generate distinct neuronal representations within the granule cells. However, since glutamatergic nor GABAergic cells in the DG are not functionally or structurally homogeneous, identifying the specific role of the different subpopulations remains elusive. Then, understanding pattern separation requires the ability to manipulate a temporal and spatially specific subset of cells in the DG and ideally to analyze DG cells activity in individuals performing a pattern separation dependent behavioral task. Thus, neurophotonics and calcium imaging techniques in conjunction with activity-dependent promoters and high-resolution microscopy appear as important tools for this endeavor. In this work, we review how different neurophotonics techniques have been implemented in the elucidation of a neuronal network that supports pattern separation alone or in combination with traditional techniques. We discuss the limitation of these techniques, and how other neurophotonic techniques could be used to complement the advances presented up to this date.